THE EFFECT OF POWER POINT PRESENTATION TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN LISTENING - Delima Suri; Iskandar Zulkarnain; wiki tedi rahmawati (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
The aim of this research was to find out the effect of power point presentation technique on the students’ achievement in listening. The research was conducted at MTs.S Nurul Amaliyah Tanjung Morawa. A quantitative with experimental was applied as the research design. The population and sample consisted of 60 students. They were divided into experimental group which was taught by using power point presentation and control group which was taught descriptively. Each group consisted of 30 students. The instrument used for collecting the data was essay cloze test by filling missing words. The test was used to obtain the students’ scores for each group. After finding the mean score, the standard deviation, and standard error of both groups, then a statistic t-test was applied. After calculating and analyzing the data, it was obtained that t-observed was 2.29 and t-table was 1.67 at t-critical 0.005 and df=58. Comparing both value, it showed that t-observed was higher than t-table (2.29>1.67) which meant that the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. This research concluded that power point presentation technique gave significant effect on students’ achievement in listening.